Bladder Tumor Contains Higher N7-Methylguanine Levels in DNA than Adjacent Normal Bladder Epithelium - Saad, Abir A.; O'Connor, Peter J.; Mostafa, Mostafa H.; Metwalli, Nabila E.; Cooper, Donald P.; Margison, Geoffrey P.; Povey, Andrew C. (Cancer epidemiology, biomarkers & prevention, 2006)
Schistosoma haematobium –infected patients are more likely to develop bladder cancer and be more exposed to carcinogenic N -nitroso compounds than uninfected patients. As N7-methylguanine is a marker of exposure to methylating agents of this type, we have measured N7-methyldeoxyguanosine 3′-monophosphate (N7-MedGp) by 32 P postlabeling. DNA was isolated from 42 paired normal and tumor tissue of Egyptians with bladder cancer. N7-MedGp was detected in DNA from 93% of the tumors and 74% of the normal bladder tissue samples. Adduct levels were highly variable and ranged from 0.04 to 6.4 and from 0.02 to 0.72 μmol/mol deoxyguanosine 3′-monophosphate (dGp) in tumor and normal DNA, respectively. N7-MedGp levels in normal and tumor DNA were highly correlated with one another ( P = 0.007). The mean difference (95% confidence interval) in adduct levels between tumor and normal DNA was 0.21 (0.13-0.32) μmol/mol dGp and this was statistically significant ( P < 0.001). The adduct ratio (tumor DNA/normal DNA) varied between 0.2 and 136 (median, 4.6). N7-MedGp levels were not associated with gender, age, or the presence of schistosomiasis. However, lower N7-MedGp levels were found in normal DNA from individuals lacking the GSTM1 gene ( P = 0.03) but not the GSTT1 gene or in subjects with the Ile105Val GSTP1 polymorphism. These results show that exposure to methylating agents is widespread and suggest that such exposure may play a role both in tumor initiation and progression. (Cancer Epidemiol Biomarkers Prev 2006;15(4):740–3)